Komparasi Efektivitas Tiga Tipe Starter Generator yang Digunakan Pada Engine Pesawat ATR - Muhammad Andi Nova; Lalu Giat Juangsa Putra; Zakki Fuadi Emzain (Institut Teknologi Dirgantara Adisutjipto, 2021)
A starter generator (DC generator) is a DC machine that acts as a motor when starting the engine and will become a DC generator when it reaches a certain speed. The DC Starter Generator will function as a starter mode when the speed is <45% NH and will become a DC generator mode when the speed is >61.5%. There are several types of starter generators on ATR aircraft: 8260-121, 8260-123, and 8260-124. The uses and functions of the three types are the same, but the maintenance schedule intervals are different. Therefore, the purpose of this study was to determine the planned maintenance intervals (brush change, bearing change, and overhaul) and the causes of differences in maintenance intervals for the starter generator. The type of research used is comparative research, where this research compares several parameters related to the planned maintenance of the Starter Generator, which will be operated within 10,000 FH. The results of the treatment intervals obtained are that types 8260-121 and 8260-123 each will require 16 times maintenance, while types 8260-124 only need 8 times maintenance. The difference in the number of treatments being less in the 8260-124 type is due to the modification of the brush. In addition, the type 8260-124 has also used a new technology commutator. Therefore, this type is superior to the other two because it can save operational aircraft costs.